Spatial analysis to identify geomorphic hazards in the southwestern Piramagrun mountain range using the (AHP) model - Ali, Prof.Dr.Peshawar Mohammed; Mohammed, Akam Majid Haji (Sulaimani Journal for Humanities, 2026)
This study focuses on the identification and classification of geomorphic hazards such as (tectonic hazards, kinetic hazards, climatic hazards) in the southwest of the Piramagrun Mountain Range. This study aims to assess the relationship between natural aspects and land use, by identifying the level of geomorphic risks and their impact on human activities and presenting appropriate solutions. For this purpose, descriptive and quantitative methods were used based on field visits to validate the data. The results showed that the area is geomorphologically unstable, with soil moisture exceeding 25 degrees in most of the hills, which has activated the phenomenon of rock collapse and landslides that have limited the development of development and roads in the area. The area is complex in terms of altitude and lowland with elevations between (714 – 2593m), with mountains (23.75%), foothills (41.19%) and plains (35.05%) of the area Removals occur. Despite the richness of the area in forests and vegetation (48.78%) and forests (45.87%), bare land (1.26%), residential areas (4.09%) that contribute to soil stability, but the threat of moving processes is clear Road projects stand out because, despite their location at moderate slopes, they are directly at risk of rock collapse and mountain slopes. The total dangerous and very dangerous area in the area has reached (54.86m) which requires a scientific engineering plan
Keywords: Geomorphic hazards; land use; southwest of Paramagnon; risk assessment